Analytical Analysis of Fractional-Order Physical Models via a Caputo-Fabrizio Operator. (20th December 2021) - Mofarreh, Fatemah; Zidan, A. M.; Naeem, Muhammad; Shah, Rasool; Ullah, Roman; Nonlaopon, Kamsing
Abstract : This paper investigates a modified analytical method called the Adomian decomposition transform method for solving fractional-order heat equations with the help of the Caputo-Fabrizio operator. The Laplace transform and the Adomian decomposition method are implemented to obtain the result of the given models. The validity of the proposed method is verified by considering some numerical problems. The solution achieved has shown that the better accuracy of the suggested method. Furthermore, due to the straightforward implementation, the proposed method can solve other nonlinear fractional-order problems.